"We are Coca-Cola and so much more": political economic analysis of non-carbonated SSB Coke brands. (20th October 2022) - Garcia, Christopher J.; Proffitt, Jennifer M.
ABSTRACT: This article utilizes critical political economy to examine how The Coca-Cola Company (Coke) constructs healthy or "natural" messages on food labels and other promotional texts to advertise non-carbonated sugary beverage brands (SSBs) owned by the company. The labeling histories and controversies of two products in particular, VitaminWater and Simply Orange Juice, are analyzed as case studies to illustrate how companies such as Coke have liberally labeled SSBs as healthy with little legal consequence. What results from labeling-related deception are consumers at risk of making ill-informed decisions about their health. However, the cases examined here reveal that current labeling regulation does little to deter from this behavior and allows for the proliferation of misleading claims.